Eco Enzyme dalam Upaya Pemanfaatan Limbah Rumah Tangga di Kelurahan Ngampel Kecamatan Mojoroto Kota Kediri - Astuti, Puji; Utami, Budhi; Puspita, Erna; Widiawati, Hestin Sri; M., Bella Ratri; Huda, Miftahul (-, 2025)
The phenomenon of rising household prices has impacted the purchasing power of all levels of society, one of which is the residents of Ngampel Village, Mojoroto District, Kediri City. This community service activity aims to reduce one of the household expenditure items, namely the purchase of liquid dishwashing soap, by utilizing household waste as eco-enzymes. Until now, residents have never utilized household waste, simply throwing it away. Over time, waste can pollute the environment. Therefore, through this activity, organic waste will be converted into eco-enzymes that can be used as liquid dishwashing soap, thereby saving one of the household expenditure items. The activity method is carried out by providing training and mentoring in making liquid soap. After the activity, participants will be able to make eco-enzymes and use them as liquid soap independently, thereby reducing monthly shopping expenses.